Strain hardening cement composites : structural design and performance : State-of-the-art report of the RILEM Technical Committee 208-HFC, SC3 - Rokugo, Keitetsu; Kanda, Tetsushi (Dordrecht ; New York : Springer)
Includes bibliographical references and index